TAZ Is Related to Postoperative In-Hospital Mortality of Acute Type A Aortic Dissection - Jiang, Wenjian; Xue, Yuan; Li, Haibin; Zhang, Hongjia; Zhao, Yuanfei (Frontiers in Cardiovascular Medicine, 2020)
Abstract Background: Surgical repair of Acute type A aortic dissection (ATAAD) has high risk and mortality, and there is few biomarker of postoperative in-hospital mortality until now. This study investigated the association between WW domain–containing transcription regulator protein 1(TAZ) and the postoperative in-hospital mortality of ATAAD patients. Methods: This is a retrospective cohort study. Data and blood samples were collected from 95 consecutive patients with ATAAD who underwent surgeries in our hospital from July 1, 2016, to December 31, 2016. The data collection included all the risk factors introduced by the modified EuroSCORE (European System for Cardiac Operative Risk Evaluation). The predictors of postoperative in-hospital death were confirmed by univariate regression analysis. Multivariable logistic regressions were used to analyze the association of the preoperative plasma level of TAZ and the postoperative in-hospital mortality of ATAAD patients. In addition, we used the generalized additive model to identify nonlinear relationships. Results: Three models were used in the multivariable logistic regression analysis of the relationship between the preoperative plasma level of TAZ and postoperative in-hospital death. In the crude model, the preoperative plasma level of TAZ showed a positive correlation with postoperative in-hospital death [odds ratio (OR)=1.33, 95% confidence interval (CI): 1.01 to 1.74, P=0.039]. In adjusted model I and adjusted model II, similar results were found (OR=1.35, 95% CI: 1.01 to 1.80, P=0.043 and OR=1.35, 95% CI: 1.01 to 1.81, P=0.039). The risk of postoperative in-hospital death in the preoperative plasma level of TAZ ≥12.7 ng/mL group was 10.08 times (OR=10.08, 95% 1.63 to 62.37; P=0.013) that of the preoperative plasma level of TAZ<12.7 ng/mL group. Conclusions: The high preoperative plasma level of TAZ suggested poor surgical prognosis for ATAAD patients. The patients with a preoperative plasma level of TAZ ≥12.7 ng/ml had much higher postoperative in-hospital mortality.